Caloric and video head impulse test dissociated results in dizzy patients - Sofia Waissbluth; Valeria Sepúlveda; Jai-Sen Leung; Javier Oyarzún (Frontiers in Neurology, 2022)
IntroductionWe are now able to detect abnormalities for any semicircular canal with the use of the video head impulse test (vHIT). Prior to the vHIT, the gold standard for unilateral canal paresis of the lateral canal was considered the caloric test. Clinical cases where the caloric test and vHIT are discordant are not uncommon.MethodsRetrospective study. All consecutive cases of dizziness seen from 11/2020 to 12/2021 for which the patient underwent both caloric and vHIT tests performed within 10 days, were reviewed. Patients with discordant results were included. We evaluated the caloric response, vHIT gains for all canals and saccades, with and without gain abnormalities.ResultsWe included 74 cases of dizziness with dissociated results. The most common finding was a normal caloric response with abnormal vHIT results (60.8%); the main abnormal finding on vHIT was the presence of saccades. In this group, 37.7% of patients had normal gains and refixation saccades. In addition, the most found low gain was for the posterior canal. The main diagnosis in this group was vestibular migraine. For the group with unilateral caloric paresis and normal vHIT gain in the lateral canal, the main diagnosis was Ménière's disease.DiscussionThe most common disorders with discordant results were Ménière's disease and vestibular migraine. The caloric test and vHIT are complementary and combining both tests provide greater clinical information. Further research is needed to understand refixation saccades with normal gains.